2007
DOI: 10.1038/sj.mt.6300100
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correction of Pompe Disease by Systemic Delivery of Adeno-associated Virus Serotype 1 Vectors

Abstract: Pompe disease is caused by a lack of functional lysosomal acid alpha-glucosidase (GAA) and can ultimately lead to fatal hypertrophic cardiomyopathy and respiratory insufficiency. Previously, we demonstrated the ability of recombinant adeno-associated virus serotype 1 (rAAV2/1) vector to restore the therapeutic levels of cardiac and diaphragmatic GAA enzymatic activity in vivo in a mouse model of Pompe disease. We have further characterized cardiac and respiratory function in rAAV2/1-treated animals 1 year post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(142 citation statements)
references
References 32 publications
4
136
1
1
Order By: Relevance
“…Studies have demonstrated that rAAV1 vectors transduce skeletal muscle more efficiently than rAAV2 vectors, and do not elicit a humoral immune response to the transgene protein (Chao et al, 2001;Mah et al, 2007). Currently, more than 90 clinical trials have begun using rAAV vectors (Ginn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that rAAV1 vectors transduce skeletal muscle more efficiently than rAAV2 vectors, and do not elicit a humoral immune response to the transgene protein (Chao et al, 2001;Mah et al, 2007). Currently, more than 90 clinical trials have begun using rAAV vectors (Ginn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A single systemic delivery of AAV-1 vectors into GAA-KO neonates led to a massive transduction of heart, diaphragm, and liver that persists over 1 yr. Supraphysiological GAA expression led to a reduction of muscle glycogen and to the improvement of cardiac functions (46). The systemic injection of AAV2/8 vectors expressing hGAA into 3 month-old immunodeficient GAA-KO/SCID mice led to massive liver transduction (47,48).…”
Section: Muscle and Liver Targeted Gene Therapymentioning
confidence: 99%
“…Mah et al 17 reported physiological improvement of the cardiorespiratory function after neonatal gene transfer of adeno-associated virus (AAV) vector, with the elicitation of anti-hGAA antibody formation that was highest at 11 weeks postinjection followed by a drop after 15 weeks and reduction to background levels by 31 weeks posttreatment. We also attempted to evaluate the physiological cardiac function of mice aged 24 weeks using echocardiography, and found no difference in the echocardiographic parameters between the Gaa À/À -untreated mice and C57BL/6-untreated mice (data not shown).…”
Section: 28-30mentioning
confidence: 99%
“…9,11 To overcome this hurdle, the use of tissuespecific promoters [12][13][14][15] and the neonatal gene transfer have been described. 16,17 Lentiviral vectors (LV) have been under active consideration for gene therapy for lysosomal storage diseases. 18 Kobayashi et al 19 reported sustained expression of enzymatically active iduronidase in multiple organs in the murine model of mucopolysaccharidosis type I after neonatal intravenous administration of LV.…”
Section: Introductionmentioning
confidence: 99%